Peran Madrasah Diniyah dalam Pembinaan Akhlakul Karimah di Madrasah Diniyah Manba'ul Ulum Dukuh Sekuwung, Kedungbanteng Ponorogo - Yulliana, Yulliana; Suyudi, M.; Samsudin, Samsudin (Social Science Academic, 2024)
Madrasah Diniyah Manba'ul Ulum in Dukuh Sekuwung, Kedungbanteng, Ponorogo, plays a significant role in fostering the moral character (akhlakul karimah) of its students through various religious programs. The background of this study highlights the importance of moral education in shaping the character of the younger generation based on Islamic values. The aim of this research is to identify and analyze the moral development programs implemented in the madrasah, the role of teachers in this process, and the impact of these programs on student behavior. This study employs a qualitative descriptive method, utilizing data collection techniques such as observation, interviews, and documentation. The findings indicate that the moral development programs, including religious studies, prayer memorization, and social activities, have successfully enhanced students' religious awareness, discipline, and social responsibility. The role of teachers as role models, mentors, and advisors is crucial in shaping students' character. Additionally, the study identifies several supporting factors such as a conducive school environment and teacher commitment, while also noting challenges such as limited facilities and parental support. The conclusion of this research is that Madrasah Diniyah Manba'ul Ulum effectively contributes to the moral development of its students, although improvements in certain areas are needed to achieve more optimal results.